Food Waste Potential as Alternative Feed Catfish Cultivation: an Overview - Pratama, Gede Agus Surya; Suryani, Sang Ayu Made Putri; Muliarta, I Nengah (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Food waste in urban areas is an endless problem, considering that waste will continue to exist. The technique of managing waste to become an alternative feed for catfish is one of the steps to overcome the problem of waste and at the same time becomes an alternative fish feed solution for fish cultivators. The purpose of this research is to process food waste into fish feed. The method used in writing this article is literature review. Based on the results of the literature review and the author's analysis, it can be concluded that food ingredients that can be processed into catfish feed are food waste by utilizing fermentation or by mixing or formulated with other raw materials such as (fish meal, magot, tofu dregs, and fine bran). The fermentation process can use fishery products sold in the market, including (EM4, Boster, etc) which are mixed with molasses.